2022
DOI: 10.1126/sciadv.abn3337
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into UV-B–activated UVR8 bound to COP1

Abstract: The CONSTITUTIVE PHOTOMORPHOGENIC 1-SUPPRESSOR OF PHYA-105 (COP1-SPA) complex is a central repressor of photomorphogenesis. This complex acts as an E3 ubiquitin ligase downstream of various light signaling transduced from multiple photoreceptors in plants. How the COP1-SPA activity is regulated by divergent light-signaling pathways remains largely elusive. Here, we reproduced the regulation pathway of COP1-SPA in ultraviolet-B (UV-B) signaling in vitro and determined the cryo-electron microscopy structure of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…In order to test whether the nuclear translocation of UVR8 requires COP1, we performed FRAP assays using previously established Arabidopsis transgenic lines expressing a YFP‐UVR8 fusion protein in the presence or absence of functional COP1 (Yin et al ., 2016 ). For this we took advantage of the COP1‐4 allele that has a premature stop codon at the position of Gln‐283; thus cop1‐4 expresses a truncated protein containing only the N‐terminal 282 amino acids including the NLS but lacking the WD40 repeats responsible for interaction with UVR8 (McNellis et al ., 1994 ; Favory et al ., 2009 ; Wang et al ., 2022 ). It should be noted that although cop1‐4 is a nonlethal, weak cop1 allele (McNellis et al ., 1994 ; Ordonez‐Herrera et al ., 2015 ), UV‐B signaling is essentially abolished in cop1‐4 (Oravecz et al ., 2006 ; Favory et al ., 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to test whether the nuclear translocation of UVR8 requires COP1, we performed FRAP assays using previously established Arabidopsis transgenic lines expressing a YFP‐UVR8 fusion protein in the presence or absence of functional COP1 (Yin et al ., 2016 ). For this we took advantage of the COP1‐4 allele that has a premature stop codon at the position of Gln‐283; thus cop1‐4 expresses a truncated protein containing only the N‐terminal 282 amino acids including the NLS but lacking the WD40 repeats responsible for interaction with UVR8 (McNellis et al ., 1994 ; Favory et al ., 2009 ; Wang et al ., 2022 ). It should be noted that although cop1‐4 is a nonlethal, weak cop1 allele (McNellis et al ., 1994 ; Ordonez‐Herrera et al ., 2015 ), UV‐B signaling is essentially abolished in cop1‐4 (Oravecz et al ., 2006 ; Favory et al ., 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…UVR8 interacts with the WD40 domain of COP1 (Favory et al ., 2009 ; Rizzini et al ., 2011 ). A recent work indicated that the structure of the COP1 WD40 domain is similar to that of RUP2 (Wang et al ., 2022 ). Surprisingly, both RUP2 and COP1 interact with UVR8 with similar interacting surface via similar key amino acid residues (Wang et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First discovered in Arabidopsis thaliana , UVR8 has been characterized as the only UV-B photoreceptor identified to date ( Kliebenstein et al., 2002 ; Rizzini et al., 2011 ; Yang et al., 2015 ). Upon UV-B absorption, ground-state UVR8 (inactive homodimer) dissociates into active monomers and rapidly interacts with the CONSTITUTIVE PHOTOMORPHOGENIC 1/SUPPRESSOR OF PHYA (COP1/SPA) E3 ubiquitin ligase complex ( Oravecz et al., 2006 ; Favory et al., 2009 ; Rizzini et al., 2011 ; Cloix et al., 2012 ; Huang et al., 2014 ; Yin et al., 2015 ; Wang et al., 2022 ). This interaction in turn inhibits the E3 ligase activity of COP1/SPA against target proteins, including the central photomorphogenesis-promoting transcription factor ELONGATED HYPOCOTYL 5 (HY5), eventually triggering the expression of UV-B-responsive genes ( Favory et al., 2009 ; Huang et al., 2013 , 2014 ; Binkert et al., 2014 ; Lau et al., 2019 ; Han et al., 2020 ; Wang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%